Konstruksi Perdamaian Antara Pengungsi Sampang Dengan Warga Desa Karanggayam Dan Bluuran Dalam Merajut Harmoni - Adila, Alannadya; Puguh Santoso; Eri R. Hidayat (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2023)
The success in resolving the Sampang Conflict of stakeholders is an outstanding achievement in building harmony in Karanggayam and Bluuran villages. This research seeks to describe the progress of the connection between Sampang refugees and villagers in ex-conflict locations through an analysis of peace construction. Using a qualitative approach, the researcher conducted direct observation and interviews to explore the peace construction happening. The result of the research shows that peace construction is realized through 1) effective channels of communication such as religious development programs and silaturrahim; 2) an effective system of arbitration through the existence of Team 5 (Five); 3) an integrative climate in religious activities portraits such as pengajian, maulud, tahlilan, and funeral ceremony; 4) a critical mass of peace enhancing leadership consisting of Regent of Sampang, Liaison Officer (LO), Ulama, and Team 5; 5) just structure by way of Ikrar.